Prevalence of positive findings of brain computed tomography scans in pediatric population - Jahanshahi, Amirreza; Sadeghvand, Shahram; Khalafi, Mohammad; Jafarzadeh, Alireza; Zarrintan, Armin (Iranian Journal of Child Neurology, 2023)
Objectives Computed tomography (CT) scans are used more frequently in medical centers, increasing unnecessary requests for it as a first-line evaluation. This study aimed to investigate the rate and prevalence of abnormal findings in a brain CT scan in children at the Children’s Hospital of Tabriz, Iran. Materials &Methods This study was a cross-sectional descriptive-analytical study that included all children under 15 years old undergoing a brain CT scan at the Children’s Hospital of Tabriz, Iran. All patients who fulfilled the inclusion criteria and were referred to the Children’s Hospital of Tabriz during the spring of 2018 entered the study. Age, gender, patient history, and clinical findings were examined. In the next step, the results of each patient’s CT scan were evaluated. Results In this study, 108 patients were studied with a median age of 18.0 months. CT scan results were normal in seventy-four cases (68.5%), hydrocephalus was seen in 15 (13.9%), and benign infantile hydrocephalus was seen in eight (7.4%). The study revealed a statistically significant relationship between patient history and CT scan results (p=0.017). A statistically significant relationship was observed between the clinical findings and CT scan results (p=0.042). Conclusion Brain CT scans have more abnormal findings in patients with positive clinical findings. Although a CT scan is a highly sensitive and specifimodality in diagnosing central nervous system (CNS) abnormalities, its value depends on the underlying medical history and physical exam.